Association between reported ADHD symptom and motor development delay in preschool children - Cui, Zhijun; Li, Shijie; Liang, Aimin; Huang, Hongmei; Ni, Xin (Frontiers in Pediatrics, 2024)
Objective: To explore whether the motor developmental level is associated with the attention deficit/hyperactivity disorder (ADHD) symptoms severity reported by parents in preschool children. Methods: Preschool children aged 4-6 years old with the chief complaint of reported inattention or hyperactivity by kindergarten teachers or parents were recruited in this study. All participants were consulted by at least one experienced developmental behavior pediatrician, according to DSM-V diagnostic criteria of ADHD. Their neuromotor developments were assessed by the Children's Neuropsychological and Behavior Scale and recorded as developmental quotient (DQ) score in gross motor, fine motor, and other domains. Regarding the evaluation of ADHD symptoms, parents of the 4-year-old group completed the Conners' Parent Symptom Questionnaire, while parents of the 5-year-old group completed The Vanderbilt ADHD Diagnostic Parent Rating Scale. Results: A total of 137 preschool children aged 4-4.9 years (4-year-old group) and 252 were aged 5.0-5.9 years (5-year-old group) were included in the study. Children exhibiting ADHD symptoms were at a much higher risk of fine motor delays compared to gross motor delays, particularly among the younger age group. Correlation analysis and hierarchical regression showed that in the 4-year-old ADHD group, better gross motor development was associated with increased severity of parent-reported ADHD symptoms. In the 5-year-old ADHD group, poorer fine motor development was linked to higher ADHD symptom severity. For children who do not meet ADHD diagnostic criteria, no significant correlations were found between gross or fine motor developmental quotients (DQ) and the severity of ADHD symptoms. Conclusions: Preschool children exhibiting ADHD symptoms are at a notable high risk of fine motor delays. Motor development in preschool children who meet ADHD diagnostic criteria is related to the severity of their symptoms. It is important to monitor both fine and gross motor development in preschool children with ADHD.